Utilization of Microarray Technology for Identification of Disease Response Genes in Banana (Musa Spp.) - Lim, Kean Jin (2006)
Banana is an important food crop in the world after cereals. In 2004, the Asia and Pacific region, Malaysia ranked 3rd for cultivated banana exporter, exporting mainly to Singapore, Hong Kong, Brunei and the Middle East. However, disease has become a major factor contributing to the declining banana industry in Malaysia. Fusarium wilt, primarily caused by Fusarium oxysporum f. sp. cubense, is a destructive disease, causing production loss of commercial banana cultivars not only Malaysia but worldwide. Up to now, no strategy has been found to effectively combat this disease. In this study, cDNA libraries for Musa acuminata x balbisiana cv Mutiara (banana Mutiara, AAB, Fusarium tolerant) and Musa acuminata x balbisiana cv Rastali (banana Rastali, AAB, Fusarium susceptible) were constructed. Five micrograms of mRNA from each banana variety was used in respective for cDNA library construction and 5000 clones from each library were randomly cored and amplified using PCR. Clones were then arrayed on glass slides and gene expression analysis was carried out. Interesting clones were randomly selected for sequencing and homology search against available databases were made. The emphasis was give to clones that have putative function in pathogen response or are pathogenesis related following Fusarium fungal infection. The cDNA microarray analysis identified 55 M. acuminata x balbisiana cv Mutiara clones that were transcriptional responsive to the Fusarium fungus infection. Several functional types of genes, including those involved in defence response, cell structure, energy, transport, signal transduction and intracellular traffic were up-regulated after Fusarium fungus infection. Clones encoded proteins that are involved in primary metabolism, protein destination and storage were down-regulated after Fusarium infection. These expression profiles show defence signalling pathways of M. acuminata x balbisiana cv Mutiara against Fusarium involved considerable interaction between different signalling pathways. Activation of defence response to Fusarium fungal attack did not involve individual gene. Additionally, many clones encoding proteins with unknown functions were identified. Functional analysis of these genes could broaden the understanding of disease resistance mechanisms of M. acuminata x balbisiana cv Mutiara defence responses to Fusarium wilt of bananas and potentially introduce candidate prevent for this disease in application to molecular breeding.